Sistem Informasi Dinas Komunikasi dan Informatika Berbasis Website - Intan Ramadhona (Jurnal Ilmu Komputer dan Sistem Informasi |JIKSI|, 2022)
In the rapidly evolving landscape of information technology, local governments, such as Palembang City Communication and Information Office (Diskominfo), must continually adapt to enhance efficiency and public service quality. Recognizing this, Diskominfo aims to implement a web-based information system, acting as a solid foundation for managing departmental activities and improving government-citizen interaction. However, challenges arise in reactivating and redesigning the Palembang website. Acknowledging the last active site in 2020, accurate updates reflecting policy changes are crucial. Navigating dynamic government and technology landscapes poses challenges in aligning information. Addressing website technology and security updates demands substantial resources, including budget and technical expertise. Effective public engagement requires a mature communication strategy. Collaborating with internal and external stakeholders poses management and coordination challenges. Thorough preparation is essential for success. The proposed solution involves a comprehensive audit for accurate updates, technology and security planning, and collaboration for a modern, user-friendly design. In conclusion, addressing content updates, technological enhancements, and communication strategies ensures the success of reactivating and redesigning the Diskominfo Palembang website, promising improved public engagement and information access.